Parkia speciosa Seeds Ethanol Extract as Co-chemotherapeutic Agent for Doxorubicin Toward Tongue Cancer - Erlina Sih Mahanani; Ikhsan Nur Arifin; Arya Nur Ihsan; Yusrina Lukitasari; Ferry Sandra (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Parkia speciosa seeds have been reported to have an anticancer property due to the presence of various antioxidant compounds. Since the potential uses of P. speciosa for the tongue cancer has not been clearly disclosed, we conducted a study to investigate anticancer properties of P. speciosa seed ethanol extract (PSSEE) as well as its effect on cardiac cells.METHODS: Tongue cancer rat model were treated with/without Doxorubicin and various concentrations of PSSEE. After treatment, tongue and heart samples were collected and processed further for histological examinations. Tongue epithelium thickness and damaged heart tissues was observed by HE staining, while tongue cancer cell proliferation was assessed by Ki-67 immunohistochemistry. Analyses were performed under an upright light microscope to measure tongue epithelium thickness, state of cancer cell proliferation, and degree of heart tissue damage.RESULTS: Addition of 400 mg/kg body weight (BW) PSSEE to 4.6 mg/kg BW Doxorubicin reduced the average tongue epithelial thickness and Ki-67+ cells number. Upon addition of PSSEE to Doxorubicin, the damage of heart tissue was reduced in a concentration dependent manner. Among all groups, the group of tongue cancer treated with 4.6 mg/kg BW Doxorubicin and 400 mg/kg BW PSSEE had the lowest percentage as well as the lowest degree of heart tissue damage.CONCLUSION: Since addition of PSSEE to Doxorubicin reduced epithelial thickness, number of Ki-67+ cells and heart tissue damage, PSSEE could be a potential co-chemotherapeutic agent for Doxorubicin toward tongue cancer.KEYWORDS: Parkia speciosa, Doxorubicin, tongue cancer, epithelial thickness, Ki-67, cardiotoxicity, co-chemotherapy